2008
DOI: 10.1063/1.2973205
|View full text |Cite
|
Sign up to set email alerts
|

Favorable pressure gradient turbulent flow over straight and inclined ribs on both channel walls

Abstract: This paper reports on experimental study of turbulent flows over straight and inclined transverse ribs of square and triangular cross sections attached to the bottom and top walls of an asymmetric converging channel. The pitch-to-height ratio of the ribs was 10. A particle image velocimetry technique was used to conduct extensive velocity measurements at channel midspan and in planes close to the leading and trailing edges of the inclined ribs. From these measurements, spatial averaged profiles of the mean vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 42 publications
0
5
2
Order By: Relevance
“…FPG leads to an increase of C f and a decrease of bulk Reynolds number. In the outer layer, competing effects of FPG and roughness were found on the mean flow and the Reynolds stresses; however, close to the rough wall, both roughness and acceleration intensify the fluctuations significantly, with the Reynolds-stress anisotropy unaffected by FPG; this was different from the observations of both Coleman et al (1977) and Tachie & Shah (2008). Similar observations on the opposite effects of FPG and roughness and the higher C f were also made from large-eddy simulations (LES) of spatially developing flows over roughness by Piomelli & Yuan (2013).…”
contrasting
confidence: 75%
See 2 more Smart Citations
“…FPG leads to an increase of C f and a decrease of bulk Reynolds number. In the outer layer, competing effects of FPG and roughness were found on the mean flow and the Reynolds stresses; however, close to the rough wall, both roughness and acceleration intensify the fluctuations significantly, with the Reynolds-stress anisotropy unaffected by FPG; this was different from the observations of both Coleman et al (1977) and Tachie & Shah (2008). Similar observations on the opposite effects of FPG and roughness and the higher C f were also made from large-eddy simulations (LES) of spatially developing flows over roughness by Piomelli & Yuan (2013).…”
contrasting
confidence: 75%
“…Similar observations in a spatially developing flow by Cal et al (2009) support this theory. Tachie & Shah (2008) also reported the increase of drag. In a sink flow, on the other hand, U RS decreases (relative to ν/k) with K due to the decrease of flow rate Q, as K = ν/Q; thus k + decreases, and the flow tends towards the hydraulically smooth regime and laminarization (Yuan & Piomelli 2014b).…”
Section: Conclusion and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The joint effects of a favourable pressure gradient and roughness on a turbulent boundary layer in the fully rough regime are of interest here. There are a number of studies in the literature focusing on the effect of mild and moderate pressure gradients on the mean and Reynolds stress profiles [24,25,26,27]. Cal et al [24] showed that the effect of roughness on the Reynolds stresses could be scaled with the friction velocity for a zero-pressure gradient and favourable pressure gradient, separately.…”
Section: Rough Wall Boundary Layer Under a Favourable Pressure Gradientmentioning
confidence: 99%
“…They also observed an increase of the roughness Reynolds number along the accelerated rough wall boundary layer, discarding the appearance of transitional effects. Tachie and Shah [25] studied a turbulent channel with two-dimensional roughness. They concluded that the effect of the pressure gradient on the mean and Reynolds stress profiles was much weaker than the effects of roughness, so that the pressure gradient could be ignored.…”
Section: Rough Wall Boundary Layer Under a Favourable Pressure Gradientmentioning
confidence: 99%